THE ASCETIC MOVEMENT IN CENTRAL ASIA DURING THE 8TH-9TH CENTURIES: RELIGIOUS AND SOCIAL PROCESSES - Gulnora Khudoyberganova (Web of Journals Publishing, 2025)
In Central Asia, asceticism emerged in the 8th–9th centuries as an independent ideological-social movement, occupying a significant place in the region’s religious, scholarly, and social life. In this article highlights of the ascetic movement in central Asia during the 8th-9th centuries: religious and social processes.
Keywords: Central Asia, asceticism, movement, religious, social process, movement, culture.